Indonesian Students’ Negotiation of Identities through Language Use in England - Komilie Situmorang (Universitas Jambi, Magister Program of English Education Department, 2020)
Study abroad (SA) is a daunting process in which students who encounter cross-border face a whole new world. They go through positioning and being positioned by others. There is an on-going salient power asymmetry in their language use, which affects their desire to speak up and participate in the new community. This study aimed to scrutinize the ways Indonesian students negotiated their identities through their language use. Using open-ended questionnaires (OEQ)and semi-structured interviews, this study focused on 7 participants who were in the midst of the master’s degree program in England. The results indicated that the participants experienced the identities negotiation multifacetedly. Participants who exercised their agency and invested in their language use challenged the positioning attached to them. As a result, they constructed new identities and gained central participation in the local community. Meanwhile, participants who could not resist the power asymmetry withdrew and formed a more solid community with other international students. Lastly, some participants were also found to maintain their emotional security by not making any contact through their language use. Participants who resisted any contacts but with fellow home students interestingly developed an increased nationalism. Therefore, this article calls for the teachers’ attention and how to devise the English Language Teaching classroom better and program providers’ of how to provide the support for the SA students best.